1990
DOI: 10.1021/jf00094a050
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in soluble fiber content of wheat fiber through enzymic modification

Abstract: The influence of fiber purification and conditions of enzymatic modification on soluble fiber content of wheat fiber were examined. Crude wheat fiber was purified by a modified enzymatic extraction. Crude wheat bran contained 16% soluble dietary fiber by weight. Purification of the crude wheat bran did not alter soluble fiber content nor result in a significant loss of total dietary fiber. A technical grade hemicellulase was used to enzymatically modify the purified wheat fiber. The yield varied considerably w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Preparation of RBDF. The preparation of RBDF was performed according to the previously described procedure 13 with some modification. Freshly prepared rice bran was obtained from Guangzhou Liquan Food Co. Ltd, Guangdong, China.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Preparation of RBDF. The preparation of RBDF was performed according to the previously described procedure 13 with some modification. Freshly prepared rice bran was obtained from Guangzhou Liquan Food Co. Ltd, Guangdong, China.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In fact soluble dietary fibre, by increas-ing the viscosity of the stomach contents, has been demonstrated to influence the rate of gastric emptying, to lower the rate of nutrient adsorption and to reduce post-prandial glycaemia and plasma cholesterol level. Enzymic treatments with the aim of increasing the soluble fibre content of wheat bran and other food by-products rich in insoluble dietary fibre have been reported (Caprez et al, 1987;Oh & Grundleger, 1990).…”
Section: Dietary Fibre and In Vitro Dry Matter Enzyme Digestibility Omentioning
confidence: 99%
“…Dietary fibers are further classified into two groups according to solubility in water: SDF and insoluble dietary fibers (IDF). Research has shown that SDF can be extracted from corn, wheat, and rice through chemical and biological treatment of the hemicellulosic fractions [5][6][7]. Potential products derived from SDF extracted from hemicellulose include emulsifiers, adhesives, thickeners, and stablizers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown reaction time and temperature to be key factors in the formation and extraction of soluble fiber from hemicellulosic sources using chemical and enzymatic treatments [2,6]. Oh et al [6] used a technical grade hemicellulase to enzymatically modify the soluble fiber content of a purified wheat fiber substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation